pH Adaptation stabilizes bacterial communities - Akihiko Mougi (npj Biodiversity)
Abstract Diverse microbes in nature play an important role in ecosystem functioning and human health. Nevertheless, it remains unclear how microbial communities are maintained. This study proposes that evolutionary changes in the pH niche of bacteria can promote bacterial coexistence. Bacteria modify the pH environment and also react to it. The optimal environmental pH level for a given species or pH niche can adaptively change in response to the changes in environmental pH caused by the bacteria themselves. Theory shows that the evolutionary changes in the pH niche can stabilize otherwise unstable large bacterial communities, particularly when the evolution occurs rapidly and diverse bacteria modifying pH in different directions coexist in balance. The stabilization is sufficiently strong to mitigate the inherent instability of system complexity with many species and interactions. This model can show a relationship between pH and diversity in natural bacterial systems.